Para Katerina Kolozova, Toward a Radical Metaphysics of Socialism: Marx and Laruelle: Towards Katerina Kolozova, Toward a Radical Metaphysics of Socialism: Marx and Laruelle - Vidal, Paulo Ricardo (Identities: Journal for Politics, Gender and Culture, 2018)
Author(s): Paulo Ricardo Vidal Title (Portuguese): Para Katerina Kolozova, Toward a Radical Metaphysics of Socialism: Marx and Laruelle Title (English): Towards Katerina Kolozova, Toward a Radical Metaphysics of Socialism: Marx and Laruelle Translated by (Portugese to English): Paulo Ricardo Vidal Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 188-193 Page Count: 6 Citation (Portuguese): Paulo Ricardo Vidal, “Para Katerina Kolozova, Toward a Radical Metaphysics of Socialism: Marx and Laruelle,” Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018): 188-193. Citation (English): Paulo Ricardo Vidal, “Towards Katerina Kolozova, Toward a Radical Metaphysics of Socialism: Marx and Laruelle,” Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018): 188-193.